Indisciplina e desenvolvimento moral na educação infantil - Franzoloso, Mariana Ribeiro (2011)
This research analyzes the relations between school indiscipline and moral development in the context of Early Child Education, following a Piagetian perspective. For this, it was developed a qualitative study that aimed to comprehend the concept of school indiscipline, in order to discern and to interpret the manifestations of this phenomenon in Early Child Education, actually, in the last year of this educational level and, also, to discover its relations with the moral development of the child. We understand indiscipline as an interacional, contextual phenomenon which causes damages for the individual or collective learning and for the social, affective and pedagogical relations in school scope and we use the theory proposed by Jean Piaget regarding the development of the morality, to help us understanding and interpreting this phenomenon. In complement to the theoretical study, we carried out a field work, observing children of 4 and 5 years old, in two public Early Child Education Schools, located in Curitiba, Paraná, as well as, interviewing teachers from the classrooms where the observations had happened, so that we could examine in the reality of the school what we read in literature and get our proper conclusions. We see indiscipline as one of the most intriguing subjects of the social and educational scope and, currently, the studies on school indiscipline reflect the importance of this subject for the Elementary and High School teachers, as well as reflect its theoretical relevance for the educational research. However, the number of researches with the focus we considered here is still restricted, which reveals the lack of investigating the proper context of Brazilian Early Child Education, knowing its characteristics and confirming the relations between moral development and indiscipline, a subject already discussed in foreigner educational literature. Our empirical inquiry lead us to find and to define typical cases of indiscipline in the Early Child Education classrooms that we observed, whose description and analysis had pointed to the relevance in considering the affective aspect, strongly involved in the expressions of indiscipline and also influential in the moral development. Through the results of our research, we learned and suggest that it is possible to identify the stage of moral development where children are, which allowed us to comprehend the moral issues and the development process of each child that may be involved with the indiscipline situations. We found out that the relations between indiscipline and moral development at the Early Child Education level involves the difficulty in accepting and following rules, in respecting each other, as well as, authority figures, the search and the necessity of bonds and for attention, and the absence of showing regulatory moral feelings such as regret, shame and guilt. These relations may suggest a lack of cooperation and mutual affection in the relationships that the child experiences, as well as, a short experience with moral values.